2018
DOI: 10.1177/0023677217750410
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on timing and velocity of rat molar eruption: Timing of rat molar eruption

Abstract: Rat molar eruption and occlusion data were compiled from several studies but several inconsistencies were found, rendering the planning of eruptional studies difficult and imprecise. Our aim was to measure eruption and occlusion days, as well as eruption velocity, in the upper and lower three molars from infancy to end of adolescence in the rat. A total of 19 male and female Wistar rats were scanned daily by micro-computed tomography (CT) from day 15 to 70. We measured the eruption of all maxillary and mandibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…We selected postnatal days 18 (P18, preocclusion eruption) and 28 (P28, 1 wk after occlusion establishment) of the Wistar rat's second root pair of the first lower molar as the study models. The eruption stage was confirmed by daily in vivo micro-CT imaging based on our previous study (Denes et al 2018). Histological analysis and micro-CT confirmed that the root development of the P18 tooth was at the initial elongation stage, while at P28, root development reached near completion (Fig.…”
Section: Pdl Has Distinct Gene Expression Profile Changes Upon Occlusion Establishmentsupporting
confidence: 60%
See 1 more Smart Citation
“…We selected postnatal days 18 (P18, preocclusion eruption) and 28 (P28, 1 wk after occlusion establishment) of the Wistar rat's second root pair of the first lower molar as the study models. The eruption stage was confirmed by daily in vivo micro-CT imaging based on our previous study (Denes et al 2018). Histological analysis and micro-CT confirmed that the root development of the P18 tooth was at the initial elongation stage, while at P28, root development reached near completion (Fig.…”
Section: Pdl Has Distinct Gene Expression Profile Changes Upon Occlusion Establishmentsupporting
confidence: 60%
“…The Wistar rat and tooth eruption stages were determined based on data of a previous study (Denes et al 2018) and verified by micro-computed tomography (CT) scans. The work was approved by the ethics committee of animal research of the Canton of Geneva (n° GE/72/15).…”
Section: Animalsmentioning
confidence: 99%
“…Based on our previous study (Denes et al, 2018), we hypothesized that the rapid change in eruption velocity seen during the transition from pre-occlusal to functional eruption may be in response to the appearance of occlusal forces. Occlusal loading influences the PDL width (Denes et al, 2013), structure (Mcculloch et al, 2000), and recovery (Terespolsky et al, 2002;Mine et al, 2005), therefore we examined differential expression during this transition to functional eruption with its first masticatory forces.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were killed by CO 2 at three time points, according to the rat molar eruption stages: daily in vivo micro-CT imaging was used to identify the pre-occlusal eruption (P18), initial occlusal contact (P21) and 1-week after occlusion (P28) with a technique previously described (Denes et al, 2018) (Supplementary Figure S1). The incisors were extracted, the mandibles were dissected and the immediately frozen with PrestoChill (Milestone R ) in cryo-embedding at −40 • C and subsequently stored at −80 • C.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation